Smoking cessation program targeting adolescents: Saudi Arabia - Al-Lehiany, O.; Stanley, David (Australian Academic Press, 2009)
While developed countries have enjoyed a decreasing incidence of smoking over the last 30years, in the developing world there are still reports of rapid smoking take-up. It seems that indeveloping countries tobacco smoking remains the number one cause of preventable death well into the future. To combat this costly habit, many governments have employed smoking cessation strategies since the 1960s. These programs have involved advertising the negative health impacts ofsmoking, increased taxation, targeted legislation, and even clinical counselling. This project aimed to explore and critically review the body of literature related to smoking cessation strategies in Saudi Arabia and assess their effectiveness. The project also aimed to use the data gathered to recommend legislative changes to smoking cessation programs. For the Saudi Arabian context, the results of the project found that the smoking cessation strategies, despite being revolutionary in many regards, still lacked depth, and that both males and females, particularly adolescents, were adopting smoking inincreasing numbers. The recommendations of the project were for Saudi Arabian authorities to review a number of the current initiatives, and initiate further approaches to smoking cessation, such as stringent requirements for health warnings on cigarette packets.